Pengaruh Biofer 2000-N dan Pupuk Kascing terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - NARTA, I K.; SUANDA, D. K.; KARTINI, N. L. (Agrotrop : Journal on Agriculture Science, 2013)
The Effects of Biofer 2000-N and Casting on Growth of Cacao (Theobroma cacao L.) Seedling. The aims of the research were to obtain Biofer 2000-N and Casting effects on growth of cacao (Theobroma cacao L.) seedling. The design used was Randomized Block Design with three replications. Treatments were allocated in factorial. First factors were four rates of Biofer: 0 g; 10 g, 20 g and 30 g/plastic bag. The second factors were four rates of Casting: 0 g, 15 g, 30 g and 45 g/plastic bag. The results showed that Biofer rate at 30 g/plastic bag, produced the highest total dry weight of seedling (21.03 mg), significantly (20.24%) higher than control (17,49 mg). Biofer at 30 g/plastic bag, increased plant height, stem diameter, stem fresh weight, leaf number, leaf area, leaf fresh weight, fresh weight of plant top, root length, fresh roots weight and total plant fresh weight respectively by 9.02%, 3.58%, 36.02%, 6.00%, 20.50%, 34.45%, 34.94%, 33.31%, 44.44%, and 34.31% than control. Casting rete at 45 g/plastic bag produced the highest dry weight of seedling (20.11 mg), significantly higher (9.89%) than control (18.30 mg).. Casting at 45 g/plastic bag, increased plant height, stem diameter, stem fresh weight, lef number, leaf area, fresh leaf weight, fresh plant top weight, root length, fresh roots weight, total plant fresh weight, respectively by 9.70%, 4.31%, 18.32%, 8.03%, 20.54%, 34.53%, 28.26%, 33.15%, 47.65% and 26.00% than control. Biofer 2000-N, Casting or both could increase cacao seedling growth, so, the seedling to be better and could be planted in the field earlier.
Keywords: Biofer 2000-N, Casting, cacao (Theobroma cacao L.)